Physiotherapy Management for Reconstruction of Anterior Cruciatum Ligament (ACL) With Achilles Graft: A Case Study - Lestari, Fegi; Maryam, Siti; Wahyuni, W (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Anterior Cruciatum Ligament (ACL) reconstruction is an action performed by performing surgery to restore the repairation function and joint stability by grafting the ACL using tendon tissue. Ligament replacement using other materials (graft) will usually be taken from the patellar tendon or hamstring tendon in the patient himself (autograft). The physiotherapy management provided is expected to be able to help the recovery process in ACL reconstruction cases.Case Presentation: Mr. G aged 38 years working as a private employee performed an ACL reconstruction with an achilles graft on his left leg which had been diagnosed with ACL rupture by doctors after performing an MRI. This injury is caused because the patient is hit by an impact during football. The operation was carried out on October 28, 2021 at Harapan Bunda Hospital. The patient after undergoing surgery one week later did physiotherapy at Esa Unggul Clinic so it still includes phase 1 rehabilitation.Management and Outcome: The physiotherapy program used cryotherapy, strengthening exercises and isometric exercises for 2 sessions/week for 4 week. The evaluation carried out the Numeric Rating Scale (NRS) to measure the pain, Manual Muscle Testing (MMT) to measure the muscle strength and goniometer to measure the Range of Motion (ROM) of knee joint.Discussion: After being given a physiotherapy program for 4 weeks, the results can reduce of pain in knee joint sinistra from 8 to 0, increasing the MMT of knee joint from 2 to 4 and increase ROM of active motion of the regio knee from the first week of S:0º - 0º - 45º to S:0º - 0º - 120º.Conclusion: Physiotherapy management in cases of ACL reconstruction with achilles graft used cryotherapy, strengthening exercise and isometric exercise can reduce pain, increase muscle strength and ROM.